COMPARATIVE ROLE OF ULTRASOUND AND COMPUTED TOMOGRAPHY IN DIAGNOSIS OF NONTRAUMATIC RIGHT ILIAC FOSSA PAIN IN PATIENTS ABOVE 50 YEARS OF AGE ADMITTED IN A TERTIARY-CARE HOSPITAL - PRASUN DAS; SUDIPTA BASU; MALAY KARMAKAR; BHATTACHARYYA, SRIJAK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to evaluate and compare the role of ultrasonography (USG) and computed tomography (CT) in diagnosing non-traumatic right iliac fossa (RIF) pain in the geriatric population. More specifically, to evaluate the diagnostic accuracy parameters of both imaging modalities after enumerating the relevant etiologies. The ultimate aim is to assess the diagnostic accuracy variables of USG in diagnosing non-traumatic RIF pain in the elderly, taking computed tomography as the gold standard of investigation. Methods: Fifty patients in the elderly age group with non-traumatic RIF pain were evaluated consecutively by USG, followed by a CT scan. Results: Overall, in detecting non-traumatic RIF pain in our study, sonography was found to have sensitivity, specificity, positive predictive value, and negative predictive value of 35.14%, 23.07%, 56.52%, and 11.1% with respect to a CT scan. It also reveals that in diagnosing the different etiologies of RIF pain, the findings of the USG have a weakly positive correlation with the findings of the CT scan. It also reveals that, on comparison between CT and USG, we found a statistically significant difference in diagnosing RIF pain in this study population. Conclusions: We therefore conclude that ultrasound may be used as an initial imaging investigation as the majority of cases of non-traumatic RIF pain come in the acute stage and emergency ultrasound comes into play due to its easy use and more availability. However, we must do a CT scan after that to narrow down the differential diagnoses in this age group.